Changes in total phenolics and total antioxidant activity of kair (Capparis decidua) fruits during maturity (Indian Journal of Arid Horticulture, 2018)
Capparis decidua (Forsk.) Edgew (Capparidaceae), determined with the Folin- Ciocalteu reagent (Medini et al.  commonly known as Kair, is a hardy plant, resistant to almost 2014) and expressed as mg GAE/g DW. Total antioxidant  all type of abiotic stresses like heat, cold, drought salinity etc. activity (TAA) of the ethanolic extract was determined by  naturally grow in arid region of India specifically Rajasthan, DPPH radical scavenging activity by following the method of  Haryana, MP, Gujarat states. This plant is also a vital Re et al. (1999) and expressed as mg Vit C equi./g DW. All  component in nutritional and income security of the rural analyses were performed in triplicate and values expressed as  peoples, especially in the arid region. Besides many the mean ± standard deviation. Data analysis was carried out  socioeconomic and ecological benefits, all parts of this plant using the analysis of variance and OPSTATE statistical  have a number of medicinal properties. The plant is computer package (www. http://hau.ac.in/about/opstat.php)
Keywords: Capparidaceae; ecological; computer